Job Satisfaction and Burnout among Intensive Care Unit Nurses and Physicians - Hilde Myhren; Øivind Ekeberg; Olav Stokland (Critical Care Research and Practice, 2013)
Introduction. Nurses and physicians working in the intensive care unit (ICU) may be exposed to considerable job stress. The study aim was to assess the level of and the relationship between (1) job satisfaction, (2) job stress, and (3) burnout symptoms. Methods. A cross-sectional study was performed at ICUs at Oslo University Hospital. 145 of 196 (74%) staff members (16 physicians and 129 nurses) answered the questionnaire. The following tools were used: job satisfaction scale (scores 10–70), modified Cooper's job stress questionnaire (scores 1–5), and Maslach burnout inventory (scores 1–5); high score in the dimension emotional exhaustion (EE) indicates burnout. Personality was measured with the basic character inventory. Dimensions were neuroticism (vulnerability), extroversion (intensity), and control/compulsiveness with the range 0–9. Results. Mean job satisfaction among nurses was 43.9 (42.4–45.4) versus 51.1 (45.3–56.9) among physicians, P<0.05. The mean burnout value (EE) was 2.3 (95% CI 2.2–2.4), and mean job stress was 2.6 (2.5–2.7), not significantly different between nurses and physicians. Females scored higher than males on vulnerability, 3.3 (2.9–3.7) versus 2.0 (1.1–2.9) (P<0.05), and experienced staff were less vulnerable, 2.7 (2.2–3.2), than inexperienced staff, 3.6 (3.0–4.2) (P<0.05). Burnout (EE) correlated with job satisfaction (r=-0.4, P<0.001), job stress (r=0.6, P<0.001), and vulnerability (r=0.3, P=0.003). Conclusions. The nurses were significantly less satisfied with their jobs compared to the physicians. Burnout mean scores are relatively low, but high burnout scores are correlated with vulnerable personality, low job satisfaction, and high degree of job stress.